Profile of the use of medicinal plants by residents of the rural area in a county at Paraná State (Research, Society and Development, 2020)
The objective of this research was to carry out an ethnobotanical study of medicinal plants used by residents of a rural area in a municipality in the State of Paraná, Brazil. 91 residents of a defined area were interviewed, from May to October 2019. For data collection, a semi-structured questionnaire was used. Qualitative data analysis was performed using the Stata 12 program. In addition to descriptive statistics, the χ2 (Chi-square) statistic was calculated to verify the association between income and use of medicinal plants and education and use of medicinal plants. The profile of those surveyed exposed the prevalence of women (91.21%), Paraná (59.34%), descendants of Italians (58.24), farmers (58.24%), Catholics (96.70%), married (72.53%), with incomplete elementary education (56.04%) and income of up to two minimum wages (58.24%). Knowledge about medicinal plants was obtained from ancestors (86.81%). The plants are used because they are natural (71.43%) and are grown mainly on the property.